Demystifying ISO 9000 - 2000 : information mapping's guide to the ISO 9000 - 2000 standard / Gerard W. Paradis and John Trubiano. - Paradis, Gerard W., 1942- (Prentice Hall PTR, 2001)
Explaining topics ranging from the certification process itself to gap analysis and corrective action, this book will help readers understand the fundamentals and the changes in the new ISO 9000 - 2000 standard.